Dimensions of Transformational Leadership in Improving the Competitiveness of Islamic Education Institutions - Saifullah, Ach.; Maunah, Binti; Patoni, Achmad; Saputra, Prayogi Restia (IAIN Ponorogo, 2023)
This study aims to describe how the Head of Madrasah performs the dimensions of transformational leadership through the Quran learning program to improve competitiveness in Madrasah Ibtidaiyah (MI) Islamiyah Ngoro Jombang. This research used the field and case study qualitative methods. The research results show that this leadership dimension includes the following: (1) idealized influence: socializing the vision, mission, and goals of Quranic learning consistently; (2) inspirational motivation: inspiring and motivating the performance of educators to consistently maintain the quality of Quranic learning; (3) intellectual stimulation: understanding internal weaknesses and external threats from various perspectives to find solutions; and (4) individualized consideration: receiving suggestions, criticisms, and complaints about the Quranic learning process and having direct dialogue with educators and parents. Implementing transformational leadership in madrasah, especially in Quranic learning, can improve the competitiveness of educational institutions. These transformational leadership attitudes make a significant contribution to developing Islamic educational institutions and increasing their competitiveness.